Are Providers PrEPed? A Retrospective Cohort Study Analyzing Retention in Care among Pre-Exposure Prophylaxis (PrEP) Patients. Issue 2 (19th September 2019) - El-Desoky, Rania H; Al-Dahir, Sara; Butler, Isolde; Sarpong, Daniel; Nawas, George T; Gillard, Christopher; Landry, Shandrika; Rady, Hamada
No abstract available